The European Dream- a More Social EU. from the Economic and Financial Crisis to Europe's 2020 Agenda - Claudia Anamaria Iov; Claudiu Marian; Claudia Maria Mera; Ioan Bogdan (CES Working Papers, 2014)
Major challenges have been created by the unprecedented international economic and financial crisis (starting Autumn 2008) with significant impact on the EU's social sector calling into question not only the banking sector, but also many of the achievements that had already been taken for granted in the EU like the Schengen Area or the Euro zone. This article argues that, in the last five years, the impact of the crisis throughout Europe has become more evident on the employment market, the relation of the majority with the immigrants, minorities and the marginal members of the society. Our approach underlines that there is a real need for increased European trans-national socio-economic cooperation and policies in order to deal with the causes of the crisis and such a “coherent European exit strategy” could be Europe 2020 Strategy.
Keywords: O52; E32; 330; EU policy-making; economic crisis; immigrants; social policy; trans-national cooperation Romania